Obstrüktif uyku apnesinde oral aparey kullanımı - Bulent Piskin; Fatih Sentut; Hakan Akin (Cumhuriyet University, 2012)
Obstructive sleep apnea is a common sleep disorder among middle-aged adults. It is characterized by repetitive collaps of upper airway obstruction during sleep. Oral appliances which used for the treatment of obstructive sleep apnea are a simple and influentual alternative for protection of upper airways from obstructions during sleep. Recently, there has been increasing interest about oral appliance usage for obstructive sleep apnea patients because of the limitations of another therapies such as positive airways pressure therapy and surgical methods. This review will be chronicled the usage of oral appliances in obstructive sleep apnea patients. Furthermore, factors which affect treatment success will be tried to discuss. Key words: Obstructive sleep apnea, oral appliances. ÖZET Obstrüktif uyku apnesi orta yaş üstü yetişkinlerde yaygın görülen bir uyku bozukluğudur. Uyku sırasında, üst hava yollarının tekrarlayan kollapsları sonucu oluşan apnelerle karakterizedir. Obstrüktif uyku apnesinde önemli bir tedavi seçeneği olan ağıziçi apareyler, uyku boyunca, üst hava yollarında oluşabilecek tıkanmaları önlemek amacıyla kullanılan basit ama etkili gereçlerdir. Son yıllarda, pozitif hava basıncı tedavisi ve cerrahi metodlar gibi diğer tedavi yöntemlerindeki kısıtlamalardan dolayı obstrüktif uyku apnesinde oral aparey kullanımına artan bir ilgi vardır. Bu derlemede, obstrüktif uyku apnesinde kullanılan oral apareyler hakkında bilgi verilecektir. Ayrıca, tedavi başarısını etkileyen faktörler tartışılmaya çalışılacaktır.